Measuring Production Function and Technical Efficiency of Onion, Tomato, and Chillies Farms in Sindh, Pakistan (The Pakistan Development Review, 2007)
Pakistan is blessed with vast agricultural resources on account of its fertile land, well-irrigated plains, huge irrigation system and infrastructure, variety of weathers, and centuries old experiences of farming. Agriculture is the single largest sector of the economy which contributes 20.9 percent in GDP and employees 43.4 percent of total work force. The estimated GDP of agricultural crops at current factor cost is Rs 1,608,522 million with major crops contributing Rs 579996 million and minor crops valued at Rs 191,835 million for the year 2006-07 [Pakistan (2007)]. The horticulture crops (fruits, vegetables and condiments) alone contribute Rs 116.645 billion, equivalent to US$ 2 billion, which is 26 percent of the total value of all crops and 81.8 percent of the total value of minor crops. Pakistan annually produces about 12.0 million tons of fruits and vegetables. Fruit and vegetable export trade in Pakistan amounts to US$ 134 million (2003-04), of which fruits account for US$ 102.7 million (76.6 percent), vegetables US$ 25.7 million (19.2 percent) and fruit and vegetable preparations (mostly juices) US$ 5.6 million which is 4.2 percent [Pakistan (2004)] .